Glutamine deprivation confers immunotherapy resistance by inhibiting IFN-γ signaling in cancer cells - Zhiwei Yuan; Taiyan Yu; Xu Wang; Kelin Meng; Tianlai Wang; Boyu Wang; Yu Xi; Congjian Wang; Chenxi Zeng; Shaojie Hu; Yitao Tian; Hui Xiong; et al. (Pharmacological Research)
Glutamine metabolism is emerging as a target for improving immunotherapy efficacy. However, the outcomes remain inconclusive. Given that the tumor-intrinsic response to interferon-γ (IFN-γ) is a key determinant of immunotherapy efficacy, we investigated whether and how glutamine deprivation in cancer cells affects their response to IFN-γ. By using human lung cancer cell lines, patient-derived tumor explants, and a syngeneic mouse model of lung cancer, we demonstrated that glutamine deprivation reduced the IFN-γ-driven response in cancer cells by promoting autophagy-dependent IFN-γ receptor (IFNGR1) degradation and rendering tumors resistant to anti-PD-1 or anti-PD-L1 therapy. Treatment with V9302, an inhibitor of the alanine-serine-cysteine transporter (ASCT2), enhanced the IFN-γ-driven response of cancer cells and increased the efficacy of PD-1 blockade therapy. Mechanistic analysis revealed that V9302 inhibited autophagy by impairing lysosomal activity independent of glutamine deprivation, likely because of its physiochemical properties, thereby preventing IFNGR1 degradation. Moreover, V9302 also increased Glut1 expression through the inhibition of lysosomal pathway-dependent degradation of Glut1 and consequently increased cancer cell glucose uptake, in turn retaining the levels of intracellular alpha-ketoglutarate (α-KG) and ATP, which are involved in maintaining IFN-γ signal transduction in cancer cells. In support of these findings, targeting lysosomal activity with chloroquine (CQ) also increased IFNGR1 expression and the IFN-γ-driven response in cancer cells. The administration of CQ increased the sensitivity of ASCT2-deficient tumors to anti-PD-L1 therapy. Glutamine deprivation per se leads to resistance to immunotherapy, whereas V9302 treatment results in increased immunotherapy efficacy through impaired lysosomal activity, which is independent of glutamine deprivation.